EFFECTIVENESS OF ASCORBIC ACID AND SALINE SOLUTION IN PEDIATRIC CENTRAL VENOUS ACCESS: RANDOMIZED CLINICAL TRIAL - Giacomozzi, Letícia Morgana; Silva, Regina Paula Vieira Cavalcante; Danski, Mitzy Tannia Reichembach; Carreiro, José Eduardo; Silva, Rodrigo Figueira da; Giacomozzi, Clélia Mozara; Wosnes, Thaline dos Reis (Cogitare Enfermagem, 2022)
Objective: to compare the effectiveness between the use of ascorbic acid and 0.9% saline solution in the prevention of pediatric central venous catheter obstruction. Method: randomized clinical trial conducted in a public hospital in Paraná, between the months of June 2018 to October 2019 with 152 participants, of which, 73 in the experimental group and 79, control group) who underwent central venous catheter insertion and randomized to receive the flush intervention with ascorbic acid or 0.9% saline solution. Results: Catheter obstruction occurred in 17 cases (11.2%), nine (11.4%) in the control group and eight (10.9%) in the experimental group. Thrombotic obstruction occurred in 15 cases, in a similar way, in both groups (p=0.88). Catheter removal occurred in 82 cases for elective reasons and in 63 cases for complications. Conclusion: the use of ascorbic acid is as efficient as 0.9% saline solution in preventing central venous catheter obstruction. The study expands the possibilities of interventions within the theme.